ظاهرة العنف تجاه الأساتذة في الإعداديات والمعاهد الثانوية : دراسة للعوامل السياقية ومحاولة لاقتراح حلول عملية - حمدي، عادل (المدرسة العليا للأساتذة آسيا جبار قسنطينة, 2016)
This study examines teh phenomenon of violence experienced by teachers on teh part of certain categories of pupils. In its first stage, it aims at probing teh contextual factors generating teh violent behaviors while trying to understand their genesis. In teh second stage, we has put forward some practical proposals for managing this phenomenon by referring to teh results of fieldwork carried out in a number of colleges and lycées, in addition to teh contributions of a literature produced in this field field.
يدرس هذا البحث ظاهرة العنف الذي يتعرض إليه الأساتذة من قبل فئات من التلامذة وهو يهدف في مرحلة أولى إلى سبر العوامل السياقية (les facteurs contextuels) التي تفرز السلوكات العنيفة ومحاولة فهم كيفية تكونها، وفي مرحلة ثانية سعينا إلى تقديم بعض الحلول العملية للتحكم في هذه الظاهرة وذلك استناداً إلى نتائج عمل ميداني أنجزناه في عدد من الإعداديات والمعاهد الثانوية بالإضافة إلى مجلوبات جملة من الأدبيات التربوية ذات صلة.
Keywords: علم النفس التربوي -- ظاهرة العنف -- العنف الطلابي -- المراهقون